2010
DOI: 10.1111/j.1467-8659.2010.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐isometric Registration of Line Features for Flexible Fitting of Protein Structures

Abstract: In this paper, we study a registration problem that is motivated by a practical biology problemfitting protein structures to low-resolution density maps. We consider registration between two sets of lines features (e.g., helices in the proteins) that have undergone not a single, but multiple isometric transformations (e.g., hinge-motions). The problem is further complicated by the presence of symmetry in each set. We formulate the problem as a clique-finding problem in a product graph, and propose a heuristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…To the best of our knowledge, the only work that performs non-affine matching between 3D line segments is done by Abeysinghe et al [1]. Unlike our method, Abeysinghe's algorithm is designed for deformations that can be represented as piece-wise near-rigid transformations.…”
Section: Related Workmentioning
confidence: 93%
See 4 more Smart Citations
“…To the best of our knowledge, the only work that performs non-affine matching between 3D line segments is done by Abeysinghe et al [1]. Unlike our method, Abeysinghe's algorithm is designed for deformations that can be represented as piece-wise near-rigid transformations.…”
Section: Related Workmentioning
confidence: 93%
“…On the other hand, it was shown that pair-wise isometry between pairs of directed segments imply isometry of whole groups of segments [1]. Hence, we impose directions on the input segments to create our graph.…”
Section: Setting Up the Graphmentioning
confidence: 99%
See 3 more Smart Citations